Assessment of rehabilitation needs in colorectal cancer treatment: Results from a mixed audit and qualitative study in Denmark. (2nd June 2016) - Wiedenbein, Liza; Kristiansen, Maria; Adamsen, Lis; Hjort, Dorte; Hendriksen, Carsten
Abstract: Background Systematic assessments of cancer patients' rehabilitation needs are a prerequisite for devising appropriate survivorship programs. Little is known about the fit between needs assessment outlined in national rehabilitation policies and clinical practice. This study aimed to explore clinical practices related to identification and documentation of rehabilitation needs among patients with colorectal cancer at Danish hospitals. Material and methods A retrospective clinical audit was conducted utilizing data from patient files randomly selected at surgical and oncology hospital departments treating colorectal cancer patients. Forty patients were included, 10 from each department. Semi-structured interviews were carried out among clinical nurse specialists. Audit data was analyzed using descriptive statistics, qualitative data using thematic analysis. Results Documentation of physical, psychological and social rehabilitation needs initially and at end of treatment was evident in 10% ( n = 2) of surgical patient trajectories and 35% ( n = 7) of oncology trajectories. Physical rehabilitation needs were documented among 90% ( n = 36) of all patients. Referral to municipal rehabilitation services was documented among 5% ( n = 2) of all patients. Assessments at surgical departments were shaped by the inherent continuous assessment of rehabilitation needs within standardized fast-track colorectal cancer surgery. In contrast, the implementation of locally developed assessment tools inspired by the distress thermometer (DT) in oncology departments was challenged by a lack of competencies and funding, impeding integration of data into patient files. Conclusion Consensus must be reached on how to ensure more systematic, comprehensive assessments of rehabilitation needs throughout clinical cancer care. Fast-track surgery ensures systematic documentation of physical needs, but the lack of inclusion of data collected by the DT in oncological departments questions the efficacy of assessment tools and points to a need for distinguishing between surgical and oncological settings in national rehabilitation policies.